Paris, the End of the Party in Alberto Blest Gana’s Los Trasplantados - Kaempfer Alvaro (De Gruyter, 2021)
Los Trasplantados [the Transplanted; the Uprooted] (1904) relates the saga of the Canalejas, a Hispanic American family that travels to France to educate their children. With the sole purpose of entering the ranks of the European aristocracy, they ultimately sacrifice one of their daughters by way of marriage. The family patriarch’s entrepreneurial vocation for social climbing, which served him well as he successfully rose into the ranks of the provincial elite in his country of origin, collapses in Paris. The Canalejas’ initial expectations of a journey give way to aspirations to integrate into Parisian high society. The narration develops as a moral narrative of the social, ethical and cultural wreckage endured by those who not only aspire to enjoy Europe at the end of the nineteenth century but also to integrate their lives into a city whose image they forged in Latin America. They sacrifice everything that connects them to their countries of origin, except for their ambition to advance socially and be recognised in their new communities and at home. Above all, the children are worse off, losing their places in a nineteenth-century vision of national aspiration.